MARKETING STRATEGY BY USING SWOT, IFE, EFE, AND QSPM METHOD TO IMPROVE COMPETITIVENESS IN SOERYA BAKERY TULUNGAGUNG - mega tunjung hapsari; didik setiawan (Jurnal Ilmiah Ekonomi Dan Bisnis, 2021)
This study aimed to analyze internal and external conditions, to develop and plan appropriate marketing strategies, as well as to improve the business competitiveness of Soerya Bakery Tulungagung. The analytical method employed was a mixed-method, which was a qualitative analysis description based on the results of the Strengths-Weaknesses-Opportunities-Threats (SWOT) matrix. Furthermore, it was supported by quantitative analysis using matrices of Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), Internal-External (IE), and Quantitative Strategic Planning Matrix (QSPM). The data collection techniques in this study employed a triangulation technique from three techniques, namely observation, interviews and literature study. The results indicated that the weighted value for the IFE matrix was 2.98 (average position) while the EFE was 3.17 (moderate position). Furthermore, in the IE Matrix, it pointed out that the strategy which should be carried out was growth and build strategy, consisting of intensive strategy (market penetration, market development, and product development) and integrative strategy (backward, forward, and horizontal integrations). Whereas, the priority strategy that might be implemented in developing this business based on the QSPM matrix was intensifying promotions and product information both online offline; improving the quality, quantity, distribution network, and partnerships; as well as opening a new branch.